A qualitative study of the attitudes of patients in an early intervention service towards antipsychotic long-acting injections. (October 2014) - Das, Amlan K.; Malik, Abid; Haddad, Peter M.
Objectives: The objective of this study was to investigate attitudinal themes to antipsychotic long-acting injections (LAIs) in patients in an early intervention team (EIT). Methods: Interviews were carried out with outpatients purposively sampled from an EIT to represent patients currently prescribed antipsychotic LAIs, oral antipsychotics and those not prescribed antipsychotic medication. Interviews were conducted and analysed according to grounded theory. Recruitment stopped when saturation of themes was reached. Results: Interviews from 11 patients were analysed (median age 24 years). Attitudes to LAIs were condensed into three key categories: therapeutic alliance and the psychiatrists' recommendation of antipsychotic medication; patients' knowledge and beliefs about LAIs; and patients' views regarding the appropriateness of LAIs. Participants valued their psychiatrist's recommendation as to the most appropriate antipsychotic. Attitudes to LAIs varied but were most positive among those currently receiving a LAI. Among those not prescribed LAIs, some were open to considering a LAI if their clinician recommended it but others were opposed to such treatment and preferred tables. There was a lack of awareness of LAIs as a treatment option among those not prescribed a LAI. Delay in being offered a LAI was reported in the group currently prescribed a LAI. Several participants associated oral antipsychotics, LAIs and mental illness with stigma. Some not prescribed a LAI had misperceptions about the nature of this treatment. Participants regarded the advantages of LAIs as convenience and avoiding forgetting to take tablets, while disadvantages included injection pain, fear of needles and coercion. Conclusion: Lack of knowledge, misperceptions and stigma related to LAIs and other treatment options should be addressed by providing patients with accurate information. This will facilitate patients being involved in choices about treatment, and should they decide to accept medication, which drug and formulation is most appropriate for their needs. Clinicians should avoid making assumptions about patients' attitudes to LAIs; attitudes vary but some early intervention patients not prescribed LAIs are open to considering this treatment. Antipsychotic prescribing should result from a shared decision-making process in which clinicians and patients openly discuss the pros and cons of different formulations and drugs. The themes identified in this qualitative study require further exploration using quantitative methodology.